Pressure knapping west of the Rhine during the Mesolithic? New evidence from Kerkhove (Belgium) - Hans Vandendriessche; Colas Guéret (PLoS ONE, 2025)
Until now, evidence for the use of pressure knapping in NW Europe during the Mesolithic has remained very scarce. In this paper, we present the technological (and functional) analysis of a new pressure knapped microbladelet assemblage from the Belgian site of Kerkhove. Attributed to the Middle Mesolithic (between 9525 and 8224 cal. BP), it marks an unexpected early appearance of this technique in the region, that strongly suggests knowledge transmission and contacts with the Maglemosian cultural area from Northern Germany and Southern Scandinavia where this technique was already present at that time. Nevertheless, based on the absolute scarcity of the evidence so far in NW Europe and based on the lack of genetic evidence, we argue that the spread of the pressure knapping technique to NW Europe did not involve large-scale demic diffusion as it was the case with its dispersal into Scandinavia. In Kerkhove, in addition, the limited size of the assemblage and the lack of other tools, cores and knapping waste related to pressure knapping and the lack of refits among the pressure knapped bladelets, indicates that it could have fulfilled a complementary role to the other lithic productions at the site, perhaps related to the (re)tooling of a very specific tool type akin to the slotted bone points/daggers known from the Maglemosian/Kongemosian area and the Baltic region.